2009
DOI: 10.1246/bcsj.82.751
|View full text |Cite
|
Sign up to set email alerts
|

Looking at Molecular Orbitals in Three-Dimensional Form: From Dream to Reality

Abstract: Over the last four decades an experimental method has been developed for looking at electron orbitals in momentum space. The method, called electron momentum spectroscopy (EMS), is based on the electron-impact ionizing reaction near the Bethe ridge at incident electron energies of the order of 1 keV or higher. This account reviews frontiers of the field, involving the first approach to molecular frame EMS that enables one to look at molecular orbitals in three-dimensional form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 180 publications
1
53
0
Order By: Relevance
“…(5) may seem to be a crude approximation for particles having Coulomb interactions, simulations have shown that calculations using the plane-wave approximation agree with those using the distorted-wave approximation provided that large momenta are transferred and that the initial momentum of the ionized electron at the instant of collision is 1.5 a.u. (i.e., near the Bethe ridge) [28,53]. The validity of this planewave approximation can also be verified experimentally by comparing (e, 2e) measurements for different energies of the incident electrons (see, e.g., Refs.…”
Section: A Electron Momentum Spectroscopymentioning
confidence: 80%
See 4 more Smart Citations
“…(5) may seem to be a crude approximation for particles having Coulomb interactions, simulations have shown that calculations using the plane-wave approximation agree with those using the distorted-wave approximation provided that large momenta are transferred and that the initial momentum of the ionized electron at the instant of collision is 1.5 a.u. (i.e., near the Bethe ridge) [28,53]. The validity of this planewave approximation can also be verified experimentally by comparing (e, 2e) measurements for different energies of the incident electrons (see, e.g., Refs.…”
Section: A Electron Momentum Spectroscopymentioning
confidence: 80%
“…However, under the so-called EMS conditions [25,26,28], as discussed below, the ionization mechanism simplifies dramatically, and, as a result, the calculation becomes much simpler. Moreover, the final expression yields a clear physical interpretation.…”
Section: A Electron Momentum Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations